Involvement of HisF in the Persistence of Acinetobacter baumannii During a Pneumonia Infection - Martínez-Guitián, Marta; Vázquez-Ucha, Juan C.; Álvarez-Fraga, Laura; Conde-Pérez, Kelly; Lasarte-Monterrubio, Cristina; Vallejo, Juan Andrés; Bou, Germán; Poza, Margarita; Beceiro, Alejandro (Frontiers in Cellular and Infection Microbiology, 2019)
Acinetobacter baumannii is currently considered one of the most problematic nosocomial microorganisms. In the present work the hisF gene from the ATCC 17978 strain and the AbH12O-A2 clinical isolate of A. baumannii was found over-expressed during the course of murine pneumonia infections. The study demonstrated that the A. baumannii ATCC 17978 mutant strain lacking the hisF gene induces a sub-lethal pneumonia infection in mice, while the complemented mutant strain increased its virulence. This histidine auxotroph mutant showed an increase on IL-6 secretion and leukocytes recruitment during infections. Furthermore, data revealed that the hisF gene, implicated in the innate immunity and inflammation, is involved in virulence during a pneumonia infection, which may partly explain the ability of this strain to persist in the lung. We suggest that HisF, essential for full virulence in this pathogen, should be considered a potential target for developing new antimicrobial therapies against A. baumannii. Importance Nosocomial pathogens such as A. baumannii are able to acquire and develop multi-drug resistance and represent an important clinical and economic problem. There is therefore an urgent need to find new therapeutic targets to fight against A. baumannii. In the present work, the potential of HisF from A. baumannii as a therapeutic target has been addressed since this protein is involved in the innate inmunity and the inflamatory response and seems essential to develop a pneumonia in mice. This work lays the groundwork for designing antimicrobial therapies that block the activity of HisF.